Discounting, Cognitive Inflexibility, and Antisocial Traits as Predictors of Adolescent Drug Involvement - Hernández, Laura; Mejía, Diana; Avila-Chauvet, Laurent (Frontiers in Psychology, 2021)
Cognitive impairments, such as steep delay discounting, have been correlated with substance-related disorders. However, antisocial traits, cognitive inflexibility, and loss discounting have been barely considered despite having a high relationship with problematic consumption. This study aims to identify the predictive power of these variables in four types of drug use. Fifty-two adolescents (age range of 13 to 19 years) were assessed with a substance involvement test, four discounting tasks using $3,000, a card sorting test, and antisocial screening. Discriminant analysis with simultaneous estimation and varimax rotation was carried out. Function one included discounting of both losses, function two AT and CI, and function three probabilistic gains. The three functions explained 60.1% of the variance. The results show that preference for small and soon punishments and larger and unlikely punishments distinguished non-use and experimental use of moderate consumption and problematic consumption. High antisocial traits and low cognitive inflexibility distinguished experimental use groups of non-use. Risk-taking did not discriminate effectively between moderate consumption and problematic consumption. A replication of this study with a larger sample size is recommended to verify the results.